Student Semiotic Representation Skills in Solving Mathematics Problems - Wa Ode Dahiana; Tatang Herman; Elah Nurlaelah; Jerito Pereira (Didaktik Matematika, 2023)
Representational transformation skills significantly influence students' success in problem-solving. Students who struggle with representational transformation skills are often less adept at utilizing mathematical ideas and relationships, and vice versa. Therefore, this study used a qualitative, descriptive-interpretive approach to examine students' semiotic representation skills when solving mathematical problems. The research was conducted in a Year 9 classroom in a public school in Bandung, Indonesia, with 30 participants divided into high, middle, and low-ability groups based on their level of mathematical ability. Data was collected using both test and interview techniques. The results indicated that students in the high and middle ability groups had adequate skills in algebraic treatment and conversion from algebra to geometry and verbal expression skills for constructing algebraic expressions and converting verbal statements into mathematical equations. In contrast, the low-ability group demonstrated a lack of semiotic representation skills in problem-solving. These findings highlight the importance of transformation and conversion skills in mathematical problem-solving activities and can be valuable information for teachers and observers of mathematics education.